SAFETY AND SECURITY ASSESSMENT USING HYBRID BELIEF RULE BASE (BRB) AS CROWD CONTROL IN PUBLIC SPACE (CASE STUDY: CROWD CONTROL AT BANDUNG RAILWAY STATION) - Elviani, Ulva
To create a judgment index that serves as a standard for decision-making, controlling crowds in public areas, such as the use of video analytics people counting, still requires additional analysis and development of the management of the generated data. Safety and security index assessment must be able to map conditions with high complexity into various possibilities. Assessment of safety and security indices must be able to map conditions with high complexity into various possibilities. The application of the Hybrid Belief Rule Base (BRB) Approach can assess the level of belief degree for each aspect of safety and security. In this study, the analysis of the belief degree on the Hybrid Belief Rule Base (BRB) was carried out by conditioning the disjunction of the conjunction implications of 27 conditions which are also known as rules. There are 3 attributes of the Hybrid Belief Rule Base (BRB) used in this study, namely people counting through video analytics, train schedules, and events. These three attributes are considered to affect the number of crowds in public spaces with the case study of the Bandung train station. The calculation of the belief degree value is carried out by aggregating data per 10 minutes from 13.00 to 17.10 WIB in four areas at the Bandung train station and on 27 to 31 October 2020 during public holidays. This study seeks to assess risks in the form of the possibility of being squeezed, fallen and stepped on, disease transmission, shortness of breath, theft, fights, and damage to facilities. From the results of the calculation of the Hybrid Belief Rule Base (BRB) that the potential risks that occur based on indexification results are pinched by 35.5%, falling and trampled 23.25%, disease transmission 43.75%, shortness of breath 38%, theft 37.4 %, fights 42.25%, and destruction of facilities 43.25%.